2020
DOI: 10.1183/13993003.03505-2020
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation at birth is associated with lung function development until age 26 years

Abstract: Little is known about whether DNA methylation (DNAm) of cytosine-phosphate-guanine (CpG) sites at birth predicts patterns of lung function development. We used heel prick DNAm from the F1-generation of Isle of Wight birth cohort (IOWBC-F1) for discovery of CpGs associated with lung function trajectories (Forced Expiratory Volume, Forced Vital Capacity, their ratio, and Forced Expiratory Flow at 25–75%) over the first 26 years, stratified by sex. We replicated the findings in the Avon Longitudinal Study of Pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…Spirometry was the primary lung function measurement used in all studies included. Eight studies conducted spirometry according to the American Thoracic Society/European Respiratory Society guidelines 3,18–24 . Eight studies reported pre‐bronchodilator measures 3,17–21,24 while one reported both pre‐ and post‐bronchodilator measures 18 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spirometry was the primary lung function measurement used in all studies included. Eight studies conducted spirometry according to the American Thoracic Society/European Respiratory Society guidelines 3,18–24 . Eight studies reported pre‐bronchodilator measures 3,17–21,24 while one reported both pre‐ and post‐bronchodilator measures 18 .…”
Section: Resultsmentioning
confidence: 99%
“…18 Epigenome-wide associations of DNA-methylation (DNA-M) at specific cytosine phosphate-guanine dinucleotide sites (CpGs) at birth and at age 7 years were observed to be associated with lung function trajectories in two studies. IOW 22,23 and ALSPAC 23 observed DNA-M of eight CpGs on genes GLUL, MYCN, HLX, LHX1, COBL, COL18A1, STRA6 and WNT11 at birth and DNA-M at 44 distinct CpGs mapped with 42 genes to be associated with FEV 1 , FVC and FEV 1 /FVC trajectories between ages 10 and 26 years, 22,23 respectively. (Tables 2 and S6 in the Supporting Information).…”
Section: Factors Associated With Lung Trajectories: Genetic Susceptibility and Family History Of Asthmamentioning
confidence: 99%
“…However, research on non-coding RNA regulated by DNA methylation in asthma is scarce. The regulation of miRNA expression by DNA methylation has been reported in many diseases of cancer, but not in asthma (18,19). For example, Tao et al have demonstrated that methylation-mediated inhibition of miR-497 promoted the progression of breast cancer (20).…”
Section: Introductionmentioning
confidence: 99%
“…However, research on non-coding RNA regulated by DNA methylation in asthma is scarce. The regulation of miRNA expression by DNA methylation has been reported in many diseases of cancer, but not in asthma ( 18 , 19 ). For example, Tao et al.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of two population-based cohorts showed differential blood DNAm of 8 CpG sites in 8 genes related to development and lung morphogenesis at birth, which were associated with lung function trajectories over the first 26 years of life [ 60 ]. This was the first study to examine health trajectories across a significant period of time, specifically at ages 10, 18, and 26 years in the Isle of Wight birth cohort, and ages 8, 15, and 24 years in the ALSPAC cohort.…”
Section: Dnam As a Potential Epigenetic Mechanism Linking Smoke Exposure Or Prenatal Stress To Childhood Respiratory Health Outcomesmentioning
confidence: 99%